PILOT STUDY: VALIDASI PENGUKURAN KOMUNIKASI KESEHATAN DALAM ANTISIPASI KERAGUAN VAKSIN DI INDONESIA - Nelia Afriyeni; Tri Rahayuningsih; Resti Wahyuni; Dwi Puspasari; Chintia Aulia Rahmah; Rico Dwi Putra Anggara (JOMIS (Journal of Midwifery Science), 2023)
COVID-19 is the dominant research topic in health communication in the last three years. The majority of discussions and activities focused on studying the application of communication strategies to inform individual decision making. However, the role of health communication in an effective and efficient way to increase one's knowledge about health risks and provide skills that encourage reducing the social impact of health communication is still lacking attention. This research aims to provide these insights because in order to solve problems related to vaccine doubts and misinformation. The focus of this research is on health communication measurement; therefore, it is important to obtain scale validation as a measurement requirement. Mixed research methods, divided into qualitative stages through open questions from the results of the literature review. Continuing quantitatively, the respondents' answers were then compiled into statement items, passed a readability test, and a scale trial. The population of this study is the Indonesian people who have received at least the first dose of the Covid-19 vaccine. The benefit of this research is to strengthen public awareness for healthy behavior and to accept vaccination programs. As a result, a health communication scale was obtained which was developed from five aspects: source, channel, message, audience, and context by Nelson's theory in 16 items through confirmatory factor analysis processed by PLS-SEM software on 319 people. Health communication has a negative relationship with Vaccine Hesitancy with an influence contribution of 53.7%. This finding can certainly be a preliminary study for further research. The next discussion is part of the task of behavioral science related to professional communication for health promotion.